Human Neural Stem Cells Reduce Hypoxia-Ischemic Neurological Impairment Through the Regulation of Inflammatory M1/M2 Microglias in Rats - Ding YB; Zhao Y; Chen BY; Wang Q; Wang ZY; Luan Z; Yi B (Neuropsychiatric Disease and Treatment)
Ya-Bing Ding,1,2,* Yuan Zhao,1– 3,* Bing-Yu Chen,1 Qian Wang,1 Zhao-Yan Wang,1 Zuo Luan,1,2 Bin Yi4 1Department of Pediatrics, The Sixth Medical Center of PLA General Hospital, Beijing, People’s Republic of China; 2Department of Pediatrics, The Second School of Clinical Medicine, Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Neonatology, Children’s Hospital of Shanxi, Women Health Centre of Shanxi, Taiyuan, People’s Republic of China; 4Department of Pediatrics, Gansu Provincial Maternity and Child-Care Hospital, Lanzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zuo Luan, Department of Peadiatric, The Sixth Medical Center of PLA General Hospital, Beijing, 100048, People’s Republic of China, Tel +86-18600310270, Fax +86-1066958303, Email luanzuodoctor@126.com Bin Yi, Gansu Provincial Maternity and Child-care Hospital, Lanzhou, Gansu, 730000, People’s Republic of China, Email www.0931@163.comObjective: This study aims to investigate the therapeutic efficacy and migration of human neural stem cell (hNSC) therapy in a rat model of moderate to severe Hypoxic-ischemic encephalopathy (HIE).Methods: hNSCs were transplanted into the brain ventricle of HIE-induced rats. The levels of vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), immunohistochemistry of M1 and M2 cells counts, as well as the apoptosis of hNSCs were conducted after 10 days transplantation. Furthermore, Hematoxylin-eosin (HE) staining and neurological function was assessed at 12 weeks post-implantation.Results: After implantation, hNSCs survived for a duration of 12 weeks. After 10 days post-implantation, extensive migration of hNSCs was observed, with a higher concentration detected in the injured hemisphere of the brain. This study also noted an upregulation in the expression levels of VEGF and BDNF in rats treated with hNSCs (P < 0.05), along with a significant reduction in M1 microglia (P < 0.001), an increase in M2 microglia (P < 0.01), and a decrease in apoptotic cell numbers (P < 0.001). At 12 weeks post-implantation, approximately 30.68% ± 4.30% of hNSCs differentiated into mature neurons, while 23.50% ± 3.60% differentiated into oligodendrocytes and 14.00% ± 1.03% differentiated into astrocytes respectively. Compared to Sham-operated rats, histological examination revealed reduced brain injury following hNSC therapy (P < 0.05). Additionally, neurobehavioral assessments demonstrated significant cognitive function recovery through Morris water maze test as well as increased frequency of left forelimb usage during Cylinder test and improved movement coordination exhibited by enhanced claw performance using Catwalk test (All P < 0.05).Conclusion: hNSCs exerted beneficial effects on brain damage recovery and apoptosis suppression via paracrine actions of VEGF and BDNF, M1/M2 microglial balance regulation, cell differentiation promotion. The study underlined the potential of hNSC implantation as a prospective neonatal HIE treatment strategy.Keywords: hypoxic-ischemic encephalopathy, neural stem cell, VEGF, BDNF, migration